Nonna Maria and the case of the stolen necklace : a novel - Carcaterra, Lorenzo (Carcaterra, Lorenzo. Nonna Maria, 2023)
"Nonna Maria sets out to clear her goddaughter's name and uncover the checkered past of an unidentifiable victim in this transporting mystery"--